Mempercantik Organ Intim: Pendisiplinan Vagina Melalui Produk Jamu Tradisional Khusus Area Kewanitaan - Shilvi Khusna Dilla Agatta (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
Abstract This article discusses the phenomenon of the use of traditional herbal medicine that is specifically used to treat female intimate organs, namely the vagina. The tradition of consuming traditional herbal medicine has been carried out for a long time on the grounds that it has many benefits and minimal risks. The main focus of this article is to discuss traditional herbal medicine as a form of disciplining women's intimate organs. Through the literature study method, the author tries to explore women's understanding of consuming traditional herbal medicine to care for their intimate organs. The results of the literature search show that vaginal discipline is a form of hierarchical control that has long grown and developed in society. Keywords : Intimate organs, traditional herbal medicine, vaginal disinfectant